2015
DOI: 10.1371/journal.pone.0132021
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm Repair with a Novel Cross-Linked Collagen Biomaterial in a Growing Rabbit Model

Abstract: BackgroundNeonates with congenital diaphragmatic hernia and large defects often require patch closure. Acellular collagen matrices (ACM) have been suggested as an alternative to synthetic durable patches as they are remodeled by the host or could also be used for tissue engineering purposes.Materials and Methods2.0x1.0 cm diaphragmatic defects were created in 6-weeks old New-Zealand white rabbits. We compared reconstruction with a purpose-designed cross-linked ACM (Matricel) to 4-layer non-cross-linked small i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…16 Primary reconstruction with living bio-tissue avoids the complications of synthetic mesh repairs. The serratus anterior muscle originates from the lateral scapula and fans anteriorly into the first nine ribs.…”
Section: Discussionmentioning
confidence: 99%
“…16 Primary reconstruction with living bio-tissue avoids the complications of synthetic mesh repairs. The serratus anterior muscle originates from the lateral scapula and fans anteriorly into the first nine ribs.…”
Section: Discussionmentioning
confidence: 99%
“…In children born with CDH requiring defect closure, a Gore‐Tex patch is the most commonly used patch (Gasior & St Peter, ). This synthetic durable material has a compliance that is different from diaphragmatic tissue, which may hamper fluid diaphragmatic movements (Mayer et al, ; Touloukian, ). Furthermore, it is not remodelled and does not grow with the neonate, thus potentially leading to reherniation, chest wall, and spinal deformities (Gasior & St Peter, ; Takayasu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In brief, a semi-rigid guide wire (TSF-35-145, 0.35”, 145cm; ® Cook medical) was passed through the vocal cords under endoscopic vision. Over it, a 10Ch (2mm) endotracheal tube was advanced blindly[ 15 ]. Due to tracheal complications (as discussed later) subsequent animals (n = 15) were intubated using a laryngeal mask airway (LMA) ( ® V-gel: R2, Millpledge, Wingene, Belgium).…”
Section: Methodsmentioning
confidence: 99%
“…Data was analyzed using Prism for Windows version 5.0 (Graphpad software, San Diego, CA, USA). A power calculation based on our previous study (tensiometry results) suggested a repair group size of n = 6 would give 80% power (independent t-test)[ 15 ]. Data was checked for normality of distribution using a Kolmogorov-Smirnov test, then presented as a mean with SD or median and IQR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation